Antibacterial activity of synthetic peptide W5(Os-C) against Staphylococcus epidermidis ATCC 35984 - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2024)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.